Barriers to women's empowerment: Case study of suburban area in Tawau, Sabah - Jain Yassin; Nurrul Fazlina Osman; Wong, Sing Yun (Human Resource Management Academic Research Society (HRMARS), 2022)
Women have important contribution in economic development. In recent years, Malaysia's female labour force participation rate has increased dramatically. However, women's economic empowerment will necessitate the removal of impediments to more productive employment for women, particularly among low-income communities. Consequently, this study aims to investigate the barriers to women's empowerment living in suburban area in Tawau, Sabah. Using a structural in-depth interview, primary data were collected from three selected key-informant respondents in Tawau, Sabah. This study summarise the issues into three themes, namely, low participation in economics activities, gender inequality, and gender violence and mental health issues. The findings of this study demonstrated the importance of a long-term policy commitment to facilitating women's empowerment in suburban areas.